369 Chimeric Antigen Receptors Deficient in Lck Signaling Require 4-1BB Costimulation to Expand in Vivo, Resist Regulatory T-Cell Suppression, and Treat Solid Tumors in Immune-Intact Hosts. (1st August 2016) - Suryadevara, Carter M.; Desai, Rupen; Farber, Samuel Harrison; Gedeon, Patrick C.; Swartz, Adam; Snyder, David; Herndon, James; Healy, Patrick; Choi, Bryan D.; Fecci, Peter Edward; Sanchez-Perez, Luis; Sampson, John H.
Abstract: INTRODUCTION: Adoptive transfer of T cells expressing chimeric antigen receptors (CARs) is an effective immunotherapy for hematological cancers but requires a rethinking for clinical efficacy against solid tumors, where CARs have largely failed. Lymphodepletive preconditioning regimens can enhance CAR activity in vivo by promoting T-cell expansion and depleting immunoinhibitory cells that counteract cellular immunity. These nonspecific regimens, however, can be exceedingly toxic and contribute to poor quality of life. Novel strategies are needed to bypass the intratumoral inhibition of CARs. CD4+FoxP3+ regulatory T cells (Tregs) play a critical role in treatment failure, and, importantly, CARs have been shown to inadvertently potentiate Tregs by providing a local source of interleukin-2 (IL-2) for Treg consumption. We explored whether specific disruption of this axis would confer efficacy against solid tumors. METHODS: We developed second (CD28z) and third (CD28-4-1BBz) generation CARs targeting the tumor-specific mutation, EGFRvIII. To eliminate secretion of IL-2, 2 amino acid substitutions were introduced in the PYAP Lck binding motif of the CD28 domain (xCD28) of CAR transgenes. We evaluated these modified second- and third-generation CARs against established B16 melanomas expressing EGFRvIII. RESULTS: Second-generation CD28z CARs fail to expand in vivo. Addition of 4-1BB in third-generation CARs improves expansion, but this modification alone was insufficient for CD28-4-1BBz CARs to treat tumors without prior host lymphodepletion. CARs deficient in Lck signaling, however, significantly retarded tumor growth in immune-intact mice without prior lymphodepletion, and this was dependent on inclusion of 4-1BB in CAR design. To determine if deficient Lck signaling altered CAR vulnerability to Tregs, we lymphodepleted mice and transferred CARs ± Tregs. Cotransfer was sufficient to abrogate the efficacy of CD28-4-1BBz CARs, whereas the efficacy of xCD28-4-1BBz CARs remained unperturbed. CONCLUSION: xCD28-4-1BBz CARs may be an effective immunotherapy for solid tumors infiltrated with Treg and may mitigate the need for toxic lymphodepletive preconditioning.